Trichoderma harzianum isolate AKH-5 enhances defense response in Cajanus cajan (L.) millsp. against Fusarium oxysporum f. sp. udum and promotes plant growth - Anil Hugar; Sreenivasa Nayaka (The Microbe)
This study investigates the integrated role of Trichoderma harzianum isolate AKH-5 as a plant growth-promoting and biocontrol agent against Fusarium oxysporum f. sp. udum, the causative agent of wilt in Cajanus cajan (L.) Millsp. (pigeon pea). AKH-5 significantly inhibited fungal mycelial growth in vitro (91.73 %), with SEM analysis revealing pathogen hyphal damage. Chemical profiling (GC–MS and FTIR) identified functional groups and metabolites-such as alcohols, long-chain esters, sterols, and cyclic sulfur- associated with antifungal activity and plant health enhancement. In addition to volatile and soluble bioactives, AKH-5 produced IAA, siderophore, ammonia, ACC deaminase, and hydrolytic enzymes (e.g., amylase, gelatinase, chitinase, cellulase, glucanase) and oxidative enzyme (catalase), confirming its growth-promoting attributes. Hypersensitivity assays validated its non-pathogenic nature. A talc-based AKH-5 formulation improved seed germination ( 93.21 ± 0.33 %) and vigour index ( 1202), while greenhouse trials confirmed enhanced seedling growth, chlorophyll content, and reduced disease severity. These findings position AKH-5 as a multifunctional bioinoculant, offering a sustainable solution for enhancing crop productivity and managing soil-borne diseases.